2018
DOI: 10.4236/msce.2018.611002
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Composites of Phosphate Glass Fibre/Nano-Hydroxyapatite/Polylactide: Effects of Nano-Hydroxyapatite on Mechanical Properties and Degradation Behaviour

Abstract: Hydroxyapatite/polylactide (HA/PLA) composites have been intensively investigated for their potential as biodegradable fixation devices to heal bone fractures. However, most of these composites failed to achieve a bone-mimicking level of mechanical properties, which is an essential demand of the targeted application. In this study, the nano-hydroxyapatite/polylactide composites were used as the matrix and continuous phosphate glass fibres (PGF) served as the major reinforcement to obtain the nano-HA/PGF/PLA hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The structural characteristics of the biocomposites are another potential explanation for the degradation of the biocomposites, which accelerates with increasing HA content. The incorporation of HA and its agglomerates can also result in a larger absorption area for water infusion, thus, enabling faster biocomposite degradation [ 10 , 68 ]. The findings of this investigation are consistent with the study performed by Donate et al [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structural characteristics of the biocomposites are another potential explanation for the degradation of the biocomposites, which accelerates with increasing HA content. The incorporation of HA and its agglomerates can also result in a larger absorption area for water infusion, thus, enabling faster biocomposite degradation [ 10 , 68 ]. The findings of this investigation are consistent with the study performed by Donate et al [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…The preferred method of degradation is a slow, steady decline of mechanical qualities that permits the mechanical load to be gradually accepted by newly formed bones, therefore, providing the essential impetus for bone with the capacity to sustain load to be renewed. To prevent the failure of bone fixation, the fast loss of mechanical properties and implant failure (premature breakdown/deformation) must be prevented [ 68 ]. After implantation, the mechanical strength of PLA/PCL/HA decreased as a result of its rapid degradation [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, it was reported that an increased HA loading in polylactic-co-glycolic acid (PLGA) led to even more pronounced pH reduction, due to the increased surface area of composites and a limited buffering ability of hydroxyapatite above the pH of 4.2 [ 26 , 29 ]. Previous work reported that the addition of HA into the PGF/PLA composite did not show any buffering effect, but led to a dramatically accelerated mechanical deterioration of composites instead [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The preferred mode of degradation is the slow, steady decline of mechanical properties that permits the mechanical stress to be gradually absorbed by newly formed bones, so providing the essential impetus for the regeneration of bone with load-bearing capability. In contrast, rapid loss of mechanical characteristics and implant failure (premature breakdown/deformation) should be avoided to prevent bone fixation failure [30]. The mechanical strength of biodegradable bone screws decreased after implantation due to their rapid rate of degradation [31].…”
Section: Resultsmentioning
confidence: 99%